2021
DOI: 10.1080/19942060.2021.1938684
|View full text |Cite
|
Sign up to set email alerts
|

Influencing mechanism of an external magnetic field on fluid flow, heat transfer and microstructure in aluminum resistance spot welding

Abstract: The magnetically assisted resistance spot welding (MA-RSW) method provides a promising approach for improving weld performance. However, the MA-RSW process involves complex multiphysics fields that make numerical modeling very challenging. Thus, most resistance spot welding (RSW) models adopt electrothermal-mechanical coupling and ignore the influence of fluid flows caused by electromagnetic forces on nugget growth. In this paper, a magnetohydrodynamic (MHD) model, which couples the electric, thermal, magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…To understand the change of nugget size in the RSW with magnetic field, the numerical simulation method was used to analyze the fluid flow mode in magnetic‐assisted RSW (MA‐RSW). [ 107,108 ] Under the action of magnetic field, the direction of the induced Lorentz force changes from the radial direction to the tangent direction around the welding joint. The simulation results of fluid flow modes of MA‐RSW and RSW are shown in Figure .…”
Section: Magnetic Field‐assisted Resistance Spot Weldingmentioning
confidence: 99%
See 4 more Smart Citations
“…To understand the change of nugget size in the RSW with magnetic field, the numerical simulation method was used to analyze the fluid flow mode in magnetic‐assisted RSW (MA‐RSW). [ 107,108 ] Under the action of magnetic field, the direction of the induced Lorentz force changes from the radial direction to the tangent direction around the welding joint. The simulation results of fluid flow modes of MA‐RSW and RSW are shown in Figure .…”
Section: Magnetic Field‐assisted Resistance Spot Weldingmentioning
confidence: 99%
“…Under the circumstances, more heat is used for diameter expansion and less for penetration because of the constant Joule heat. [ 108 ] Besides, the simulation results indicated that the nugget shape is influenced by the local fluid flow mode, but the local fluid flow mode is dominated by the magnetic field distribution. Therefore, the nugget in MA‐RSW can grow toward the edge with increasing magnetic flux density.…”
Section: Magnetic Field‐assisted Resistance Spot Weldingmentioning
confidence: 99%
See 3 more Smart Citations